Functionalized Microparticles Producing Scaffolds in Combination with Cells. (4th November 2013) - Custódio, C. A.; Santo, V. E.; Oliveira, M. B.; Gomes, M. E.; Reis, R. L.; Mano, J. F.
<x xml:space="preserve">Abstract</x> The development of biologically instructive biomaterials with application for tissue regeneration has become the focus of intense research over the last years. This work reports a novel approach for the production of three‐dimensional constructs for tissue engineering applications based on the assembly of chitosan microparticles exhibiting specific biological response with cells. Chitosan microparticles with a size range between 20 and 70 μm are functionalized with platelet derived growth factor (PDFG‐BB). The functionalization is achieved by previous immobilization of an anti‐PDGF‐BB antibody, using a water‐soluble carbodiimide. When incubated with a cocktail of growth factors‐platelet lysates, the previously functionalized particles are able to target PDGF‐BB from the protein mixture. In vitro studies are carried out focusing on the ability of these systems to promote the assembly into a stable 3D construct triggered by the presence of human adipose stem cells, which act as crosslinker agents and induce the formation of a hydrogel network. The presence of immobilized growth factors gives to this system a biological functionality towards control on cell function. It is also bioresponsive, as cells drive the assembly process of the microgel. These versatile biomimetic microgels may provide a powerful tool to be used as an injectable system for non‐invasive tissue engineering applications with additional control over cellular function by creating specific microenvironments for cell growth.